RELATIONSHIP OF BREAKFAST WITH STUDENTS' CONCENTRATION SDN TONDO PALU IN CENTRAL SULAWESI - Gayatri, Cynthia; Sumarni, Sumarni; Mutiarasari, Diah (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2018)
ABSTRACT Background: Balanced nutrition can increase their endurance, intelligence and make normal growth. A healthy person has the intellect and the power of daily activities is quite high, especially for schoolchildren, which will help them in improving concentration and intellectual ability. Increasing the concentration of learning can be achieved in various ways, one of them is breakfast. Breakfast relate to mental intelligence, in a sense, the breakfast brought positive effects on brain activity, and the brain becomes more intelligent, more sensitive and easier to concentrate. Aim: To determine the relationship of breakfast with students' concentration SDN Tondo Palu in Central Sulawesi. Method: Types of research methods used in this research was analitic corelatonal. Sampling was done by total sampling method. The samples were students of class V and VI SDN Tondo that can communicated well and were in good health and willing to be the subject of researched. The study began with the distribution of Informed Consent to students of class V and VI SDN Tondo, followed by filling the questionnaire by the student and last performed concentration test was using grid concentration test. Results: From the result of questionnaires it was found that respondents who did breakfast as many as 53 students (53.5%) and the results of research on the concentration of learning obtained the students with the highest concentration of learning are in the moderate concentration category that is 52 students (52.5%). Based on the correlation results obtained significance value 0.003 <0.05 which means that there is a significant value relationship between breakfast with the concentration of learning. Conclusion: There is a significant relationship between breakfasts with a concentration of study to students at SDN Tondo Palu in Central Sulawesi. Keywords: Breakfast, Concentration of study